Stereotactic radiofrequency ablation of tumors at the hepatic venous confluence. Issue 7 (July 2022) - Schullian, Peter; Johnston, Edward; Laimer, Gregor; Scharll, Yannick; Putzer, Daniel; Eberle, Gernot; Kolbitsch, Christian; Amann, Arno; Stättner, Stefan; Bale, Reto
Abstract: Background: Radiofrequency ablation (RFA) is subject to "heat-sink" effects, particularly for treatment of tumors adjacent to major vessels. Methods: In this retrospective study, 104 patients with 137 tumors (40 HCC, 10 ICC and 54 metastatic liver tumors) close to (≤1 cm from) the hepatic venous confluence underwent stereotactic RFA (SRFA) between June 2003 and June 2018. Median tumor size was 3.7 cm (1.4–8.5) for HCC, 6.4 cm (0.5–11) for ICC and 3.8 cm (0.5–13) for metastases. Endpoints comprised safety, local tumor control, overall and disease-free survival. Results: The overall major complication rate was 16.0% (20/125 ablations), where 8 (40%) were successfully treated by the interventional radiologist in the same anesthetic session and did not prolong hospital stay. 134/137 (97.8%) tumors were successfully ablated at initial SRFA. Local recurrence (LR) developed in 19/137 tumors (13.9%). The median and overall survival (OS) rates at 1-, 3-, and 5- years from the date of the first SRFA were 51.5 months, 73.5%, 67.0%, and 49.7% for HCC, 14.6 months, 60.0%, 32.0% and 32.0% for ICC and 38.1 months, 91.4%, 56.5% and 27.9% for metastatic disease, respectively. Conclusion: SRFA represents a viable alternative to hepatic resection for challenging tumors at the hepatic venous confluence.